High-stake conditions to catalyse local sustainable development through Fablabs in Africa - Mboa Nkoudou, Thomas Hervé (My University, 2022)
The chapter argues that a technology cannot be fully appropriated if it is not decolonized. Looking into the maker movement, the author specifically explores the creation of Fablabs and their development in Africa to define the conditions of innovation and technology appropriation. So-called techno-coloniality can manifest itself through the coloniality of knowledge, technology transfer, techno-utopian discourse and neo-capitalist practices. It is required that digital technologies contribute to sustainable local development through the pursuit of cognitive justice, inclusion, empowerment, decoloniality, collaboration with the informal sector and commons-based governance. The chapter attempts to define appropriate technologies from a decolonial perspective as not part of the logic of techno-coloniality, but with clear local societal purpose and contributions.
Keywords: Sustainable development; Fablabs; Techno-coloniality